Pesantren-Based Economic Empowerment Model in Realizing Economic Independence - Nursani Alvia Siregar; Mustapa Khamal Rokan; Waizul Qarny (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The pesantren economy is an economic concept in which pesantren will manage and develop businesses with various innovations, which can be profitable for pesantren and generally very beneficial for the community in realizing economic independence. The purpose of this research is to find out the pesantren-based economic empowerment model implemented at the Modren Al-Hasimiyah Darul Ulum PEMADU Islamic Boarding School and also to find out what challenges Pemadu Islamic Boarding School will face in empowering the pesantren economy in realizing economic independence. This type of research uses descriptive qualitative methods with a case study strategy. The data collection techniques used in this research are interviews, observation, and documentation. The results of this study indicate that Pondok Pesantren Modren Al- Hasimiyah Darul Ulum PEMADU applies a pesantren-based economic empowerment model that has a significant effect on the economic independence of pesantren, and religious development. So that from various units or activities carried out by the pesantren, it has indirectly provided education and teaching to the community inside and outside the pesantren.